2007
DOI: 10.1111/j.1475-1305.2007.00354.x
|View full text |Cite
|
Sign up to set email alerts
|

Stiffness and Reinforcement Effect of Electrical Resistance Strain Gauges

Abstract: The increasing use of low‐modulus materials, on which the reinforcement effect of the electrical resistance strain gauge is not negligible, has re‐opened the research interest into this issue. This study deals with the evaluation of stiffness, and of the strain gauge Young's modulus involved in the estimation of both the global and the local reinforcement effect; the relationship between the strain gauge stiffness and the local reinforcement effect is also analysed. In particular, the experimental technique us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…One may observe similar reinforcement effects caused by a traditional electrical resistance strain gauge bonded on a specimen which is made of low modulus material. Ajovalasit et al [11,12] indicated that the electrical resistance strain gauge alters the strain distribution near the strain gauge location, i.e. the local reinforcement effect, when the specimen has a relatively large cross-section and is made of low modulus material.…”
Section: Introductionmentioning
confidence: 99%
“…One may observe similar reinforcement effects caused by a traditional electrical resistance strain gauge bonded on a specimen which is made of low modulus material. Ajovalasit et al [11,12] indicated that the electrical resistance strain gauge alters the strain distribution near the strain gauge location, i.e. the local reinforcement effect, when the specimen has a relatively large cross-section and is made of low modulus material.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, to avoid the influence of the end effects it advisable to limit properly the ratio k = L f /L r . Taking into account that for the examined cases the ratio k = 0.4, that is, L f = 60 mm, in Table 2 the corrective coefficients provided from the proposed theory (equation (28)) are compared with those obtained from numerical results. Table 2 shows also the two cases that will be considered in the successive experimental analysis.…”
Section: Comparison Between Theoretical Model and Numerical Resultsmentioning
confidence: 99%
“…By substituting equation (36) into equation (28) and then the resulting equation into equation (37), and after simple, algebra the following formulas are obtained…”
Section: Correction Factor Cmentioning
confidence: 99%
See 2 more Smart Citations